2017
DOI: 10.1016/j.jpsychires.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Risperidone versus olanzapine among patients with schizophrenia participating in supported employment: Eighteen-month outcomes

Abstract: This study compares the efficacy and tolerability of olanzapine versus risperidone among patients with schizophrenia who are established in outpatient psychiatric care and entering supported employment. A multicenter, randomized, double-blind trial was conducted among 107 outpatients with schizophrenia, who were cross-titrated to flexible dose risperidone or olanzapine over 2 weeks. Clinical endpoints included time to hospitalization and persistence on assigned medication. Weight, laboratory tests, psychopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…After removing duplicates and examining titles and abstracts, we selected 514 records for full‐text assessment. Of these, 100 primary studies were eligible for inclusion (corresponding to 99 full‐text articles 57‐155 , as one paper reported on two trials). Of these, 92 studies, including 22,645 participants, provided data for ≥1 outcome of interest (see Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…After removing duplicates and examining titles and abstracts, we selected 514 records for full‐text assessment. Of these, 100 primary studies were eligible for inclusion (corresponding to 99 full‐text articles 57‐155 , as one paper reported on two trials). Of these, 92 studies, including 22,645 participants, provided data for ≥1 outcome of interest (see Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Altogether, we included 63 reports (59 randomized studies) with 45,787 participants (median: 255 participants/study, range: from 12 to 18,154) (Table ). The mean age of the population was 37.6±7.0 years; 62.1±13.3% were male and 61.1±28.8% were white.…”
Section: Resultsmentioning
confidence: 99%
“…Our finding reinforces the relevance of monitoring patients with schizophrenia over time and assessing the importance of a possible superiority of one antipsychotic over the other, except for the possible adverse events of each one. This hypothesis was verified in the study by Noordsy et al where olanzapine and risperidone showed similar efficacy among stable patients and in outpatient follow-up study, with no statistically significant differences between the causes for discontinuation of treatment [55]. In addition, there was also no significant difference between olanzapine and risperidone in some analyzes performed in the CATIE studies regarding all causes of discontinuation of treatment, including lack of effectiveness, in patients with schizophrenia [56,57].…”
Section: Discussionmentioning
confidence: 75%